2016
DOI: 10.9790/0853-150722125
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Thyroid Dysfunction in Patients with Type2 Diabetes Mellitus in A Tertiary Care Hospital (Faamch, Barpeta, Assam, India)

Abstract: Background: Diabetes mellitus is one of the most common metabolic disorder with its increasing incidence world wide. Thyroid dysfunction is another common endocrine disorder frequently encountered in clinical practice(1). The association between diabetes mellitus and thyroid disorder is widely known. Under this backdrop, the present study was undertaken with the following aims and objectives. 1) To know the prevalence of thyroid dysfunction in Type 2 diabetes mellitus. 2)To know the spectrum of thyroid dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(8 reference statements)
0
0
0
Order By: Relevance
“…Thyroid dysfunction is another common endocrine disorder frequently encountered in clinical practice worldwide, second only to diabetes [7,8]. The association between type 2 diabetes mellitus (T2DM) and thyroid dysfunction (TD) has been reported in the medical literature since 1979 [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid dysfunction is another common endocrine disorder frequently encountered in clinical practice worldwide, second only to diabetes [7,8]. The association between type 2 diabetes mellitus (T2DM) and thyroid dysfunction (TD) has been reported in the medical literature since 1979 [9].…”
Section: Introductionmentioning
confidence: 99%
“…The association between type 2 diabetes mellitus (T2DM) and thyroid dysfunction (TD) has been reported in the medical literature since 1979 [9]. The prevalence of thyroid dysfunction varies widely at the community level in different countries, ranging from 6.6% to 13.4% [7]. Many studies have reported varying prevalences (10%-24%) of thyroid dysfunction in type 2 diabetes [10].…”
Section: Introductionmentioning
confidence: 99%